2021
DOI: 10.3390/foods10071662
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CaCl2 Treatment Alleviates Chilling Injury of Loquat Fruit (Eribotrya japonica) by Modulating ROS Homeostasis

Abstract: The effects of calcium chloride (CaCl2) treatment on chilling injury (CI), reactive oxygen species (ROS) metabolism, and ascorbate-glutathione (AsA-GSH) cycle in loquat fruit at 1 °C storage for 35 d were investigated. The results indicated that CaCl2 treatment remarkably suppressed the increase in browning index and firmness as well as the decrease in extractable juice rate. CaCl2 treatment also decreased the production of superoxide radical (O2•−), hydrogen peroxide (H2O2) content, but increased the 1,1-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…Hence, AA can be used as a stabilizer of the network of AEAs [15]. The results are in line with other studies conducted on peach [49,72], persimmon fruit [73], and banana [44].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence, AA can be used as a stabilizer of the network of AEAs [15]. The results are in line with other studies conducted on peach [49,72], persimmon fruit [73], and banana [44].…”
Section: Discussionsupporting
confidence: 90%
“…By modulating SOD, POD, CAT, and the AsA-GSH cycle, CaCl 2 increased chilling tolerance in green peppers [79]. A previous study on loquat fruit found that CaCl 2 treatment increased cold tolerance by regulating energy metabolism and accumulating osmotic substances [72,80].…”
Section: Discussionmentioning
confidence: 92%
“…Our results on the lower expression levels of SODCC.1 in water-stressed plants treated with the novel biostimulant, compared to plants treated with the standard CaCl2 fertilizer, are following these last observations. Anyway, several studies on calcium chloride applications have shown the capacity of this mineral fertilizer to induce increased activities and gene expressions of superoxide dismutase and catalase which are protecting from oxidative stress produced by cold, pathogens, and drought ( Xu et al, 2013 ; Shi et al, 2014 ; Chakraborty et al, 2017 ; Hou et al, 2021 ). Nevertheless, we did not observe a significant up-regulation of superoxide dismutase following SOB02 treatments in WW conditions and the physiological results in our experiment seem to encourage the interpretation of the lower expression of SODCC.1 gene in SOB01 plants as a reduction of the water stress susceptibility of the plants.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium chloride was already considered as having a positive effect on ROS homeostasis in loquat fruit (Eribotrya japonica). The authors suggested that CaCl 2 treatment alleviated chilling injury through rising antioxidant enzyme activities and the ascorbate-glutathione (AsA-GSH) cycle system to scavenge ROS [41], which could, therefore, prevent the lipid peroxidation.…”
Section: Physiological Disordersmentioning
confidence: 99%